In vitro sensitivity of oral, gram-negative, facultative bacteria to the bactericidal activity of human neutrophil defensins. - Miyasaki, K T (1990)
Neutrophils play a major role in defending the periodontium against infection by oral, gram-negative, facultative bacteria, such as Actinobacillus actinomycetemcomitans, Eikenella corrodens, and Capnocytophaga spp. We examined the sensitivity of these bacteria to a mixture of low-molecular-weight peptides and highly purified individual defensin peptides (HNP-1, HNP-2, and HNP-3) isolated from human neutrophils. Whereas the Capnocytophaga spp. strains were killed significantly by the mixed human neutrophil peptides, the A. actinomycetemcomitans and E. corrodens strains were resistant. Killing was attributable to the defensins. The bactericidal activities of purified defensins HNP-1 and HNP-2 were equal, and both of these activities were greater than HNP-3 activity against strains of Capnocytophaga sputigena and Capnocytophaga gingivalis. The strain of Capnocytophaga ochracea was more sensitive to defensin-mediated bactericidal activity than either C. sputigena or C. gingivalis was. The three human defensins were equipotent in killing C. ochracea. C. ochracea was killed under aerobic and anaerobic conditions and over a broad pH range. Killing was most effective under hypotonic conditions but also occurred at physiologic salt concentrations. We concluded that Capnocytophaga spp. are sensitive to oxygen-independent killing by human defensins. Additional studies will be required to identify other components that may equip human neutrophils to kill A. actinomycetemcomitans, E. corrodens, and other oral gram-negative bacteria.